Analyzing Time Complexity in Image Fusion through Deep Learning Mechanisms - T.R.Rajesh, Himanshu Kumar Diwedi, P.Lokesh Kumar Reddy, N.Phani Kumar (International Journal of Advanced Science and Technology, 2020)
The advent of image analysis and research in the field of image research comes with many scientific protocols. The investigation of image and their properties has very complex task to understand in microscopicview.Thepixelhasthesmallestsizewhichiselementarypartoftheimagestudy.Imagefusion isthemostemergingfieldofthisanalysis.TheInformationofanykindwhetheritisimageordatamustbe clear on receiver side. The image fusion is the technique which collect the images at various angle and integrated the image to make a perfect image which reflect the non-degradable or near to original image. Simply the integrated images much give the full-fledged information of the need area which can’t possible in single shot of image. This paper demonstrates the three techniques which are Compressive Bilateral Filter (CBF), ConvSR and Weighted least squares (WLS) of image fusion experimented through MATLAB. The three technique is belonging to the deep learning techniques. This paper investigates the time ofexecution of fusion process of images. The exploration provides the comparative time differences of three techniques in fusion process. This paper includes the twenty-one images pairs. The pairing of image fused through the said techniques provide the single image which consist the both image features withnon-degradation.